Epidermal Electronics: Materials and Optimized Designs for Human‐Machine Interfaces Via Epidermal Electronics (Adv. Mater. 47/2013). (December 2013) - Jeong, Jae‐Woong; Yeo, Woon‐Hong; Akhtar, Aadeel; Norton, James J. S.; Kwack, Young‐Jin; Li, Shuo; Jung, Sung‐Young; Su, Yewang; Lee, Woosik; Xia, Jing; Cheng, Huanyu; Huang, Yonggang; et al.
<x xml:space="preserve">Abstract</x> Thin, soft, and elastic electronics, which have physical properties well matched to the epidermis, can be conformally and robustly integrated with the skin. Materials and optimized design of such devices are presented for surface electromyography (sEMG) by J. A. Rogers and co‐workers on page 6839. The skin‐integrated electronics shown here enable use of sEMG for advanced forms of human‐machine interfaces. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>